Is tourism in fashion? Weaving knowledge about the relationship between tourism and fashion - Claudino, Adson de Lima; Lanzarini, Ricardo (Tourism and Hospitality International Journal, 2024)
Fashion and tourism are contemporary phenomena that symbolize the transformations in society, stemming from the socio-cultural and economic relations of their surroundings. In an attempt to elucidate the synergy between these two fields of study, this theoretical essay discusses whether and how there is a correlation between tourism and fashion. By establishing a link between the two, a collaborative relationship is envisioned, in which each sector benefits the other directly or indirectly. The study points out that fashion and tourism move in the field of subjective emotions, conceiving desire, pleasure, luxury and experiences as aptitudes that favor their consumption and expansion.